The scale for the prediction of aggression and dangerousness in psychotic patients (PAD): a prospective pilot study - Bjorkly, Stal (Criminal justice and behavior, 1994)
The Scale for the Prediction of Aggression and Dangerousness in Psychotic Patients (PAD) is a rating scale constructed for the assessment of psychotic patients in relation to 29 situations or interactions. The instrument is used to rate the potential of these situations/interactions for precipitating aggressive behavior in psychotic patients. These assessments result in a profile of situational vulnerability that describes a patient's potential for aggressive behavior in relation to the 29 situations or interactions. In this pilot study, 10 psychotic patients at a special secure unit were assessed by means of this scale. After the completion of the PAD ratings, systematic observations of episodes involving verbal, threatened, and physical aggression were made throughout a 2-year follow-up period. The results indicate that the PAD was able to predict the patients' potential for aggression and, to some extent, the situations that were the most potent precipitants of aggressive behavior